RESOURCE-SAVING AND WASTE-FREE TECHNOLOGIES AS THE BASIS FOR IMPROVING THE EFFICIENCY OF PROCESSING INDUSTRY OF THE REPUBLIC OF DAGHESTAN - A. D. Ibragimov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The paper presents the results of studies of production of the main products of the food and processing industry of the Republic of Daghestan, is considered the modern crisis of the industry and proposes measures of State support for the industry.